Só mais um episódio: um estudo sobre o comportamento do consumidor que maratona e a relação entre o apego às séries e à marca de plataforma de streaming - Trevisan, Nathally Cristina (2025)
Video streaming platforms have transformed the way audiences consume audiovisual content and have driven the popularization of bingue-watching, characterized by the sequential viewing of multiple episodes in a single session. Seeking to deepen the understanding of this phenomenom, this study invesigates the relationship between bingue-watching behavior, brand attachment to streaming platform, and content attachment. The research follows a quantitative design, using a structured questionaire applied to 286 participants. After scale validation tests (Exploratory and Confirmatory Factor Analysis) and Spearman correlation analysis, the results indicate that bingue-watching behavior is positvely associated with content attachment and that content attachment, in turn, has a stronger relationship with brand attachment is significant but weaker, suggesting that plattform loyalty depends not only on consumption behavior but also on the emotional connection with the available content. This finding highlights the importance of exclusive content curation as a key strategy for user engagement and subscriber retention.